Análisis Prospectivo de la Detección Hiperespectral de Cultivos de Arroz (Oryza Sativa L.) - Serrano, Jorge; Fábrega, José; Quirós, Evelyn; Galán, Javier Sánchez-; Jiménez, José Ulises (KnE Engineering, 2018)
The objective of this work is to perform a prospective analysis of the wavelengths that can be used to recognize a rice crop due to its phenological status and variety. For this purpose, field measurements of spectral signature in the 350 nm -1049 nm range were employed. The rice cultivars FCA 616FL and IDIAP 54-05 were used. The study site was located in the Juan Hombrón area in the Coclé province, Panama. A principal component analysis (PCA) was carried out, which resulted in the lengths 728.16, 677.89 and 785.48 nm let phenological differentiation within the cultivar FCA 616FL and IDIAP 54-05, the lengths 729.72, 814.58 and 666.81 nm let distinguish between crop varieties FCA 616FL and IDIAP 54-05 in vegetative phase. Keywords: Rice, reflectance, hyperspectral signature, phonological state.